Adverse Behavioral Adaptation to Adaptive Forward Collision Warning Systems: An Investigation of Primary and Secondary Task Performance. (October 2020) - Reinmueller, Katharina; Kiesel, Andrea; Steinhauser, Marco
Highlights: Adaptive FCWs adjust warning timing to the driver´s current distraction state Driving simulator study evaluated behavioral adaptation to an adaptive FCW Adaptive FCW induced adverse behavioral adaptation in longitudinal control System feedback induced increased secondary task engagement Abstract: Advanced driver assistance systems can effectively support drivers but can also induce unwanted effects in behavior. The present study investigates this adverse behavioral adaptation in adaptive Forward Collision Warning (FCW) systems. Other than conventional FCW systems that provide warnings based on static Time-To-Collision (TTC) thresholds, adaptive FCW systems consider the driver's need for support by adjusting warning thresholds according to distraction. A neglected question is how drivers adapt their behavior when they use adaptive FCW systems under realistic conditions, i.e., when warnings occur infrequently but system functionality is anticipated. Forty-eight participants drove with two different FCW systems (adaptive vs. non-adaptive) while working on a secondary in-vehicle task in a driving simulator. During the main part of the experiment, no brake events occurred and hence FCW functioning was largely anticipated. Additionally, visual system feedback about the driver's distraction state was manipulated between groups. Participants had significantly shorter minimal time-headways and TTCs when driving with the adaptive relative to the non-adaptive system. Participants with system feedback about distraction state spent generally more time with engaging in the secondary task. These results indicate behavioral adaptation which, however, is restricted to the task that is specifically supported by the system, namely longitudinal control.